Anticancer effects of disulfiram in T‐cell malignancies through NPL4‐mediated ubiquitin–proteasome pathway. Issue 4 (1st April 2022) - Chen, Cunte; Nie, Dingrui; Huang, Youxue; Yu, Xibao; Chen, Zheng; Zhong, Mengjun; Liu, Xin; Wang, Xianfeng; Sui, Songnan; Liu, Zhuandi; Tan, Jiaxiong; Yu, Zhi; et al.
Abstract: T‐cell malignancies, including T‐cell acute lymphoblastic leukemia (T‐ALL) and T‐cell lymphoma (TCL), are characterized by inferior treatment effects, high heterogeneity, poor prognosis, and a lack of specific therapeutic targets and drugs to improve outcome. Disulfiram (DSF) is a drug used to clinically control alcoholism that has recently been shown to be cytotoxic for multiple cancers. However, the underlying effects and mechanisms of DFS treatment in patients with T‐cell malignancies are not well characterized. In this study, we report that DSF promotes apoptosis and inhibits the proliferation of malignant T‐cell cell lines and primary T‐ALL cells. We provide evidence that DSF exerts anticancer activity in T‐cell malignancies by targeting the NPL4 ‐mediated ubiquitin–proteasome pathway. Notably, high expression of NPL4 and 2 ubiquitin–proteasome pathway genes, anaphase‐promoting complex subunit 1 ( ANAPC1 ) and proteasome 26S subunit ubiquitin receptor, non‐ATPase 2 ( PSMD2 ), was significantly associated with unfavorable overall survival (OS) for patients with TCL and T‐ALL ( p < 0.05). More importantly, the weighted combination of NPL4, ANAPC1, and PSMD2 could visually display the 1‐, 3‐, and 5‐year OS rates for patients with T‐cell malignancies in a nomogram model and facilitate risk stratification. Specifically, risk stratification was an independent predictor of OS for patients with T‐cell malignancies. In conclusion, DSF might induce apoptosis and inhibit the proliferation of malignant T‐cells via the NPL4‐mediated ubiquitin–proteasome pathway and offer a potential therapeutic option for T‐cell malignancies. Graphical Abstract: Disulfiram eradicates T‐cell malignancies by targeting the NPL4‐mediated ubiquitin‐proteasome pathway, and NPL4, ANAPC1, and PSMD2 might be potential biomarkers for risk stratification.